SYMPTOMATIC THERAPY OF COUGH DURING SEASONAL INCREASE OF ACUTE RESPIRATORY INFECTIONS PREVALENCE - K. S. Volkov; L. S. Namazova-Baranova; N. I. Voznesenskaya; V. A. Barannik; K. E. Efendieva (Вопросы современной педиатрии)
Cough is the main symptom of the respiratory tract disorders. Mostly it occurs in viral, bacterial and mixed (viral and bacterial) respiratory tract infections. The highest rates of respiratory tract infections are among children: it is known that children have respiratory tract infections 3–4 times as much as adults. Available drugs used in acute respiratory tract infections are numerous and various and cover almost all methods of influence on the infectious process. Nowadays the problem of usage of effective and at the same time safe agents in acute respiratory tract infections in children is very topical. The modern approaches to treatment of acute respiratory tract infections in children are discussed in the article. A special attention is given to symptomatic therapy. The authors describe the approaches to treatment of cough according to its character, intensity and other characteristics.